Algorithm for resource allocation and computing offloading in 6G networks: deep reinforcement learning-based - Saeed, Mamoon M; Saeed, Rashid A; Ali, Elmustafa Sayed; Mokhtar, Rania A; Khalifa, Othman Omran (IEEE, 2024)
The emergence of the sixth generation (6G) wireless networks brings new challenges and opportunities for efficient computing offloading and resource allocation. This paper proposes a novel Deep Reinforcement Learning-based Computing Offloading and Resource Allocation (DRL-CORA) algorithm for 6G networks. The algorithm leverages the power of deep reinforcement learning to dynamically determine the optimal computing offloading decisions and resource allocation strategies. The Deep Reinforcement Learning-based DCORA algorithm for computation offloading and resource allocation is effective, as demonstrated by our simulations. When compared directly, the suggested DCORA algorithm performs 15% better than other baseline systems.